Pengaruh Struktur Modal, Pertumbuhan Penjualan, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Yahya Nuur Hidayat; Hapzi Ali (Dinasti Review, 2024)
The effect of capital structure, sales growth and firm size on firm value is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Capital Structure has an effect on Firm Value; 2) Sales Growth has an effect on Firm Value; and 3) Firm Size has an effect on Firm Value.